Abscisic acid analogs as chemical probes for dissection of abscisic acid responses in Arabidopsis thaliana. (May 2015) - Benson, Chantel L.; Kepka, Michal; Wunschel, Christian; Rajagopalan, Nandhakishore; Nelson, Ken M.; Christmann, Alexander; Abrams, Suzanne R.; Grill, Erwin; Loewen, Michele C.
Graphical abstract: ABA analogs altered at positions around the ring have been tested against thirteen RCARs and four PP2Cs and in representative physiological assays in Arabidopsis . Highlights: Abscisic acid (ABA) is a hormone involved in plant development and stress response. 12 ABA analogs were screened against 3 plant assays and 13 Arabidopsis receptors. ( S )-ABA-like analogs retained activity in receptor assays, ( R )-ABAs were inactive. PBI352, 1′-OCH3 ether of ( S )-ABA, is selective for stomatal closure in Arabidopsis . Broader ABA analog screening has potential in plant growth regulator development. Abstract: Abscisic acid (ABA) is a phytohormone known to mediate numerous plant developmental processes and responses to environmental stress. In Arabidopsis thaliana, ABA acts, through a genetically redundant family of ABA receptors entitled Regulatory Component of ABA Receptor (RCAR)/Pyrabactin Resistant 1 (PYR1)/Pyrabactin Resistant-Like (PYL) receptors comprised of thirteen homologues acting in concert with a seven-member set of phosphatases. The individual contributions of A. thaliana RCARs and their binding partners with respect to specific physiological functions are as yet poorly understood. Towards developing efficacious plant growth regulators selective for specific ABA functions and tools for elucidating ABA perception, a panel of ABA analogs altered specifically on positions around the ABA ring was assembled. These analogs have been used to probe thirteen RCARs and four type 2C protein phosphatases (PP2Cs) and were also screened against representative physiological assays in the model plant Arabidopsis. The 1′-O methyl ether of ( S )-ABA was identified as selective in that, at physiologically relevant levels, it regulates stomatal aperture and improves drought tolerance, but does not inhibit germination or root growth. Analogs with the 7′- and 8′-methyl groups of the ABA ring replaced with bulkier groups generally retained the activity and stereoselectivity of ( S )- and ( R )-ABA, while alteration of the 9′-methyl group afforded an analog that substituted for ABA in inhibiting germination but neither root growth nor stomatal closure. Further in vitro testing indicated differences in binding of analogs to individual RCARs, as well as differences in the enzyme activity resulting from specific PP2Cs bound to RCAR-analog complexes. Ultimately, these findings highlight the potential of a broader chemical genetics approach for dissection of the complex network mediating ABA-perception, signaling and functionality within a given species and modifications in the future design of ABA agonists.